South Triangle Learning Commons - Babst, Earvin Kyle P.
The South Triangle Learning Commons is a learning facility which aims to combine and integrate educational, commercial, and residential spaces into one facility. The project hopes to not simple put the different spaces are able to operate harmoniously and promote learning through interaction and collaboration while at the same time, create civic spaces wherein the community may develop. The design approach utilized by the thesis batch of 2017 is that of an agenda-based response wherein a specific district and eventually site was identified. The agenda, which were formulated based on the information about the site, acted as the main guiding force for the thesis project. With this approach, the thesis batch of 2017 aims to develop new building typologies that combine the different functions of existing spaces and structures.